The impact of flipped teaching on EFL students’ academic resilience, self-directed learning, and learners’ autonomy - Izadpanah, Siros (Frontiers in Psychology, 2022)
Abstract This study was an attempt to investigate the impact of flipped teaching on EFL academic resilience, self-directed learning, and learners’ autonomy. To do this, the researcher selected 354 participants by the two-stage cluster sampling method. This research was quasi-experimental based on pretest, post-test, and control groups. Three questionnaires were administered to collect data: the academic resilience of Samuels (2004), a self-directed assessment questionnaire by Fisher et al. (2001), and the autonomy questionnaire by Zhang and Li (2004). The questionnaires were analyzed using SPSS 24 software and inferred analysis of covariance (ANCOVA). The study of covariance showed that flipped teaching had a significant effect on the variables of academic resilience, self-directed learning, and learner’s autonomy in learning with the help of the pre-test covariate variable (p<00.5). Also, the mean scores of students in the pre-test and post-test in the experimental group were significantly different. The mean scores of EFL students’ academic resilience, self-directed learning, and learner autonomy were higher through flipped teaching. It is suggested that school principals provide the ground for teachers' participation in workshops on new teaching strategies so that teachers can benefit from new teaching approaches, including flipped teaching in the classroom.